Economic And Political Determinants Of Public Procurement Corruption In Developing Countries: An Empirical Study From Uganda - Basheka, Benon C. (Journal of Public Procurement., 2011)
This paper examines the economic and political determinants of public procurement corruption in Uganda. Using data from 548 respondents in the public, private and NGO sectors of Uganda, the paper identifies critical economic and political determinants of public procurement corruption in Uganda. All over the world, the attention of policy makers, academics, development partners, the general public, civil society organizations and politicians has been drawn to the negative effects of corruption on development and the delivery of effective services. Corruption; a phenomenon as old as man himself (Shabbir & Anwar, 2007) has recently risen to the top of the development agenda, particularly in the developing economies. It is this recognition that leads to investigation of why corruption exists and what makes it so differently widespread among countries (Serra, 2004). Unlike in the past where corruption research was the preserve of economists and political scientists, today other disciplines like public procurement have significant interest. This paper compares the emergent results with local and international literature. It presents a number of theoretical and managerial implications for addressing the “disastrous monster” of procurement corruption in the context of the developing world.